2018
DOI: 10.1038/s41531-018-0053-5
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Parkinson’s disease sleep symptoms and daytime somnolence after bilateral subthalamic deep brain stimulation in Parkinson’s disease

Abstract: Introduction: Deep brain stimulation (DBS) markedly improves motor function in advanced Parkinson’s disease (PD), but its effect on sleep is less clear. Patients and methods: Forty PD patients who had subthalamic DBS (STN-DBS) were identified from an on-going non-motor naturalistic longitudinal study (NILS). All patients were followed up for at least 6 months, 26 patients had a 1 year follow-up. A total PDSS score of 100 or less, a score in any PDSS-item of 6 or less, and a Epworth score of 10 or more were cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…More than half of the target population reported poor sleep quality on the subjective questionnaire used in the study. It is in accordance with the results of previous studies done on this topic 12,18 . It is an eye opener for the clinicians in our set up as neurologists usually miss this inquiry from the Parkinsonism patients and psychiatrists are seldom involved in the management of these patients in our set up.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More than half of the target population reported poor sleep quality on the subjective questionnaire used in the study. It is in accordance with the results of previous studies done on this topic 12,18 . It is an eye opener for the clinicians in our set up as neurologists usually miss this inquiry from the Parkinsonism patients and psychiatrists are seldom involved in the management of these patients in our set up.…”
Section: Discussionsupporting
confidence: 93%
“…Non probability consecutive sampling technique was used to gather the sample. Screening was performed on all the patients of PD between the age of 50 and 80 years reported for follow up visit or referred from other centers, diagnosed 11,12 at least 6 months ago by a consultant neurologist. Patients outside the designated age bracket, or those with previous significant psychiatric or substance use history or those delirious or had dementia at the time of interview were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…In 10 patients with 3 months of follow-up, PDSS showed improved sleep quality but, unlike our findings, without improvement of excessive daytime sleepiness 36 . In two other studies using PDSS, one showed improved scores for daytime sleepiness, sleep quality, and restless legs syndrome (n = 17) at 6 months postoperatively 37 , and the other showed significant improvements in PDSS after 6 months (n = 40) but not after 12 months (n = 26) 38 .…”
Section: Discussionmentioning
confidence: 94%
“…Improvement in sleep and pain was also observed in dystonia patients who were treated with STN DBS [75]. Interestingly, daytime sleepiness does not seem to be affected by DBS [76]. A possible reason for this could be a lacking effect on REM sleep, as DBS patients have an increased risk of developing REM sleep behavioral disorder in the case of STN stimulations [77].…”
Section: Sleepmentioning
confidence: 93%